SEROPREVALENCE OF INFECTION BY HEPATITIS VIRUSES B AND C IN BLOOD DONNORS FROM THE NORTHERN REGION OF RIO DE JANEIRO STATE. - Motté, Marcos Oliosi (2018)
Introduction: Due to the frequent absence of symptons in its acute stage, most part of viral hepatitis diagnosis are done inadvertently through blood donations or pre-surgical triage. Goal: Original in the state´s northern region, the study defined the Hepatitis B and C´s seroprevalence among blood donors from Ferreira Machado´s hospital blood donor center. Metodology: It is an analytical cross-sectional study done through an analysis of Ferreira Machado´s blood center donors data from 2004 to 2015. The markers analyzed were anti-HBc and anti-HCV (IgG and total). Results: A total of 86.815 samples were analyzed. Among them, 54.585 (62.9%) were male and 32.230 female. The anti-HBc positive prevalence was 2.86% (2488), having the most prevailing anti-HBc positive from 40 to 49 years old (25.76%, p<0.0001). In regard to anti-HCV, the prevalence was 0.67% (581), having an affected age group from 30 to 39 years old (38%, p<0.0001). The seropositivity  prevalence for the anti-HBc and anti-HCV markers was higher among men (74,1% and 70.6%, respectively). Conclusion: When compared to the hepatitis prevalences among the selected triennium  (2004-6, 2007-9, 2010-12 and 2013-15), we noticed a national average, the northern region shows a low positivity to the anti-HCV and compatible numbers to the other regions of the country in regard to the anti-HBc.